Polymorphism of tmprss2 (rs12329760) and severity of COVID-19 in the Ukrainian population: Response - Izmailova, Olga; Shlykova, Oksana; Kabaliei, Alina; Vatsenko, Anastasia; Ivashchenko, Dmytro; Dudchenko , Maksym; Volianskyi , Andrii; Zelinskyy, Gennadiy; Koval, Tetiana; Dittmer, Ulf; Kaidashev, Igor (Acta Biomedica Atenei Parmensis, 2023)
.